2017
DOI: 10.1103/physrevlett.119.016401
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Realization of Type-II Dirac Fermions in a PdTe2 Superconductor

Abstract: A Dirac fermion in a topological Dirac semimetal is a quadruple-degenerate quasi-particle state with a relativistic linear dispersion. Breaking either time-reversal or inversion symmetry turns this system into a Weyl semimetal that hosts double-degenerate Weyl fermion states with opposite chiralities. These two kinds of quasi-particles, although described by a relativistic Dirac equation, do not necessarily obey Lorentz invariance, allowing the existence of so-called type-II fermions. Recent theoretical discov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
212
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(231 citation statements)
references
References 38 publications
14
212
0
5
Order By: Relevance
“…TaIrTe 4 [55] and LaAlGe [56] were also demonstrated to hold type-II Weyl fermions. Recently, the band structure with highly tilted cone has also been found in type-II Dirac semi-metals [57][58][59][60][61].…”
Section: Type-ii Weyl Semi-metal Statesmentioning
confidence: 91%
“…TaIrTe 4 [55] and LaAlGe [56] were also demonstrated to hold type-II Weyl fermions. Recently, the band structure with highly tilted cone has also been found in type-II Dirac semi-metals [57][58][59][60][61].…”
Section: Type-ii Weyl Semi-metal Statesmentioning
confidence: 91%
“…PdTe 2 is a layered compound forming by the stacking of layers composed of {PdTe 6 } octahedral as in PdTe. More recently, Noh et al reported the existence of type-II Dirac fermions in PdTe 2 by angle-resolved photoemission spectroscopy combined with ab initio band calculations [9].…”
Section: Introductionmentioning
confidence: 99%
“…

Recent levels of interest in topological semimetals (TSMs) have stimulated a fruitful avenue of research in materials science. [12][13][14][15] The concept of broken Lorentz invariance also results in a new system termed type-II DSM, in which the Dirac cones are tilted significantly along specific momentum directions, [16][17][18][19][20][21][22][23] leading to a modulated effective mass and the potential for new applications. [12][13][14][15] The concept of broken Lorentz invariance also results in a new system termed type-II DSM, in which the Dirac cones are tilted significantly along specific momentum directions, [16][17][18][19][20][21][22][23] leading to a modulated effective mass and the potential for new applications.

…”
mentioning
confidence: 99%
“…[24][25][26][27] In particular, intrinsic topological superconductivity (TSC) [28][29][30][31][32][33] could be induced in type-II DSMs due to a finite density of states around the Dirac points, potentially hosting Majorana modes [28][29][30][31][32][33][34][35][36][37] with possible applications in topological quantum computations. [16,[18][19][20][21] These materials are group-10 transition-metal dichalcogenides (TMDC), with crystal structures belonging to the 3 l P m space group, offering similar electronic structures consisting of type-II Dirac dispersions protected by C 3v symmetry. [16,[18][19][20][21] These materials are group-10 transition-metal dichalcogenides (TMDC), with crystal structures belonging to the 3 l P m space group, offering similar electronic structures consisting of type-II Dirac dispersions protected by C 3v symmetry.…”
mentioning
confidence: 99%
See 1 more Smart Citation